Identification of a new gene locus for adolescent nephronophthisis, on chromosome 3q22 in a large Venezuelan pedigree - Omran, Heymut; Fernandez, Carmen; Jung, Martin; Häffner, Karsten; Fargier, Bernardo; Villaquiran, Aminta; Waldherr, Rüdiger; Gretz, Norbert; Brandis, Matthias; Rüschendorf, Franz; Reis, André; Hildebrandt, Friedhelm (The American journal of human genetics, 2000)
Nephronophthisis, an autosomal-recessive cystic kidney disease, is the most frequent monogenic cause for renal failure in childhood. Infantile and juvenile forms of nephronophthisis are known to originate from separate gene loci. We describe here a new disease form, adolescent nephronophthisis, that is clearly distinct by clinical and genetic findings. In a large, 340-member consanguineous Venezuelan kindred, clinical symptoms and renal pathology were evaluated. Onset of terminal renal failure was compared with that in a historical sample of juvenile nephronophthisis. Onset of terminal renal failure in adolescent nephronophthisis occurred significantly later (median age 19 years, quartile borders 16.0 and 25.0 years) than in juvenile nephronophthisis (median age 13.1 years, quartile borders 11.3 and 17.3 years; Wilcoxon test P=.0069). A total-genome scan of linkage analysis was conducted and evaluated by LOD score and total-genome haplotype analyses. A gene locus for adolescent nephronophthisis was localized to a region of homozygosity by descent, on chromosome 3q22, within a critical genetic interval of 2.4 cM between flanking markers D3S1292 and D3S1238. The maximum LOD score for D3S1273 was 5.90 (maximum recombination fraction .035). This locus is different than that identified for juvenile nephronophthisis. These findings will have implications for diagnosis and genetic counseling in hereditary chronic renal failure and provide the basis for identification of the responsible gene.